Laparoscopic management of auto-amputated ovarian cyst in an infant - T K Jayakumar; Rahul Saxena; Taruna Yadav; Neha Satyaprakash Mathur; Arvind Sinha (African Journal of Paediatric Surgery, 2024)
The routine schedule of antenatal ultrasound scans has led to an increased frequency of detection of foetal ovarian cysts. Although most of them regress spontaneously, some may grow into large cysts and undergo torsion followed by auto-amputation. However, pre- and post-natal scans may fail to identify this event. We report a case of a prenatally diagnosed ovarian cyst that failed to resolve conservatively and was increasing in size in post-natal ultrasounds. Pre-operative ultrasound and magnetic resonance imaging failed to detect the auto-amputation. The diagnosis was confirmed on laparoscopy which offers a safe and effective method for the removal of ovarian cysts in neonates and infants.